Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2010
DOI: 10.1111/j.1464-410x.2010.09442.x
|View full text |Cite
|
Sign up to set email alerts
|

Clinicopathological outcomes after radical cystectomy for clinical T2 urothelial carcinoma: further evidence to support the use of neoadjuvant chemotherapy

Abstract: Study Type – Therapy (case series)
Level of Evidence 4 What’s known on the subject? and What does the study add? Systemic chemotherapy for muscle‐invasive bladder cancer is underutilized. Currently, debate centers on whether patients should be given neoadjuvant chemotherapy or be given chemotherapy after surgery, depending on the pathology of the specimen. In this paper, we found that greater than 73% of patients had evidence of bladder cancer that was locally advanced, a criteria that would designate these … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(24 citation statements)
references
References 29 publications
1
22
0
1
Order By: Relevance
“…We found that abnormal imaging was a strong independent predictor and control for other predictors, those patients with hydronephrosis had nearly fourfold increases in the risk of advanced MIBC. The independent prognostic value of hydronephrosis was further confirmed in another series of cT2 disease as predictor of extravesical disease 24 these factors in our scoring system resulted in the AUC of 0.79, which is statistically better than a model including only variables proposed by Karakiewicz et al 4 and similar to other reports (0.79-0.85) 1,3,6,7 .…”
Section: Discussionsupporting
confidence: 87%
“…We found that abnormal imaging was a strong independent predictor and control for other predictors, those patients with hydronephrosis had nearly fourfold increases in the risk of advanced MIBC. The independent prognostic value of hydronephrosis was further confirmed in another series of cT2 disease as predictor of extravesical disease 24 these factors in our scoring system resulted in the AUC of 0.79, which is statistically better than a model including only variables proposed by Karakiewicz et al 4 and similar to other reports (0.79-0.85) 1,3,6,7 .…”
Section: Discussionsupporting
confidence: 87%
“…The neutrophil-to-lymphocyte and platelet-to-lymphocyte ratios have been shown to be valuable prognostic markers in patients with various types of tumors [4-9], including bladder cancer [10,11]. Risk stratification based on clinicopathologic data is insufficient to support treatment-related choices in patients with bladder cancer [12]. Novel prognostic markers that aid in stratifying patients and making treatment-related decisions are therefore necessary.…”
Section: Introductionmentioning
confidence: 99%
“…Another reason to offer NC to patients with cT2 disease is that a significant number of patients are upstaged at the time of RC. Contemporary series show that up to 73% of patients with cT2 disease are actually upstaged at RC, 27 and as such may derive greater relative benefit from NC than initially expected preoperatively. Encouraging data from a recent Canadian survey of medical oncologists and urologists suggests that 96% and 88%, respectively would offer NC, however the referral rate and use of NC is still relatively low.…”
Section: Patient Selection For Ncmentioning
confidence: 99%